Pathological mechanisms of polyglutamine disorder in Drosophila model of Huntington disease - Lin, Yu-Hsien (Jihočeská univerzita, 2020)
The first publication in my thesis surveyed the impacts of adenosine homeostasis and its underlying mechanisms in Huntington disease (HD) pathogenesis using a Drosophila model. In the second publication, we have extended the use of HD model flies to monitor mHTT effects on innate immune response.
Pathological mechanisms of polyglutamine disorder in Drosophila model of Huntington disease
Keywords: adenosine; Huntington disease; Drosophila; polyglutamine; adenosine; Huntington disease; Drosophila; polyglutamine